Pengaruh Sales Promotion, Store Atmosphere, Dan Kualitas Pelayanan Terhadap Impulse Buying Pada Konsumen Alfamart Kota Magelang - Hasan Atmajaya; Andhatu Achsa; Yacobo P Sijabat (Universitas Medan Area, 2023)
Changes in consumption behavior in the world are currently experiencing a shift. There have been changes in the economy, consumer lifestyles, attitudes and shopping patterns of consumers have changed from traditional to modern. The retail business is one of the end-level goods and services distribution businesses, which will be directly enjoyed by consumers. Minimarket is the most dominating retail business in Indonesia. Understanding consumer behavior is a strategy to survive and face the intense competition in the business world, one of which is impulse buying or unplanned purchases.. This study aims to determine the effect of Sales Promotion, Store Atmosphere, and Service Quality on Impulse Buying. The population in this study are Alfamart retail consumers in Magelang City. The sample in this study was 100 respondents using purposive sampling method. This research uses primary data by distributing questionnaires to respondents. The data analysis technique uses multiple linear regression analysis. The software tool used in the research is SPSS. The results of this study prove that there is a significant influence between Sales Promotion and Service Quality variables on Impulse Buying. Meanwhile, the Store Atmosphere variable has no significant effect on Impulse Buying. While simultaneously the variables Sales Promotion, Store Atmosphere, and Service Quality have a significant effect on Impulse Buying.